2014
DOI: 10.12720/jomb.3.2.78-83
|View full text |Cite
|
Sign up to set email alerts
|

Docking Study of β-glucosidase B (BglB) from P. Polymyxca with Cellobiose and Cellotetrose

Abstract: Beta-glucosidase (3.2.1.21) plays an essential role in the removal of non-reducing terminal glucosyl residues from sacharides and glycosides. Recently, beta-glucosidase has been of interest for biomass conversion that acts in synergy with two other enzymes, endo-glucanase and exoglucanase. However, there is not much information regarding the molecular interactions of beta-glucosidase with cellobiose. Thus, this study reports on the binding modes between beta-glucosidase from glycoside hydrolase family 1 namely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…Earlier, Haq and colleagues [4] using different docking models showed that BglA of T. petrophila contained two or three conserved Glu residues (Glu 166, 351, and 405) in close contact to the substrate to catalyze the reaction. In our studies, Glu166 and Glu405 were in hydrophobic contact with cellobiose and may have a role in recognition of inhibitors, as reported earlier by Mazlan and Khairudin [7]. Moreover, Trp122, Glu166, Gly224, Tyr294, Tyr295, Trp324, Phe414, and Glu405 ( Fig.…”
Section: Discussionsupporting
confidence: 87%
“…Earlier, Haq and colleagues [4] using different docking models showed that BglA of T. petrophila contained two or three conserved Glu residues (Glu 166, 351, and 405) in close contact to the substrate to catalyze the reaction. In our studies, Glu166 and Glu405 were in hydrophobic contact with cellobiose and may have a role in recognition of inhibitors, as reported earlier by Mazlan and Khairudin [7]. Moreover, Trp122, Glu166, Gly224, Tyr294, Tyr295, Trp324, Phe414, and Glu405 ( Fig.…”
Section: Discussionsupporting
confidence: 87%
“…The cellobiose structure was obtained from the ZINC database (http://zinc.docking.org). 61 For each system, we used grid sizes of 60 × 98 × 56 (X, Y, Z), centered at the geometric center occupied by the catalytic triad. This considerable grid size was selected to contain all residues suggested in the literature relevant to substrate interactions and obtain a sufficient margin for the structural changes in the different protein constructions at different temperatures 7,62 .…”
Section: Methodsmentioning
confidence: 99%